(untitled) (Journal of Hama University, 2022)
The aim of the research is to find out the level of exposure to bullying among a sample of workers with motor disabilities in government departments and the differences between them according to the variables (age, gender, number of years of service). The sample consisted of (30) male and female workers with disabilities, and they were divided into groups according to For sex within two groups (8) females and (22) males, as well as within three age groups, which are a group (25-20 years), a group (30-26 years) and a group (31 years and over). A sample of workers in government departments with disabilities, and the research results indicated that there are statistically significant differences between the average scores of workers with disabilities on the scale of bullying behavior at the level (0.05) according to the younger age group, and also that there are no statistically significant differences between The average of the study sample on the scale of bullying behavior at the level (0.05) according to the gender variable, with statistically significant differences in physical and material bullying in favor of males, and in emotional and social bullying in favor of females.